Surface modified nanodiamond and method for producing surface modified nanodiamond

By closing the polyglycerol chain ends of the nanodiamond surface modification group, the problem of poor dispersion of nanodiamond in the low-polar solvent in the prior art is solved, and excellent dispersion in the low-polar solvent is achieved.

CN113993612BActive Publication Date: 2025-03-11DAICEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080041280.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-05
Filing Date
2020-06-03
Publication Date
2025-03-11
Estimated Expiration
2040-06-03

AI Technical Summary

Technical Problem

The prior art is difficult to achieve good dispersion of nanodiamonds in low polarity solvents, especially the polarity of surface modified nanodiamonds introduced with polyglycerol chains is too high, limiting the dispersion medium used.

Method used

The polyglycerol chain ends of the polyglycerol chain surface modification nanodiamond are blocked with alcohol, isocyanate or carboxylic acid chloride to form a surface modification group with a polyglycerol chain whose hydroxyl end is not blocked, thereby achieving excellent dispersion in low-polar solvents.

Benefits of technology

Excellent dispersion of nanodiamonds in low-polar solvents is achieved, and the range of dispersion media available for nanodiamonds is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113993612B_ABST
    Figure CN113993612B_ABST
Patent Text Reader

Abstract

The present invention provides a polyglycerol chain surface-modified nanodiamond having excellent dispersibility in a low-polarity solvent and a method for producing the same. The surface-modified nanodiamond (1) comprises a nanodiamond particle (2) and a surface-modifying group (3) for surface-modifying the nanodiamond particle (2), wherein the surface-modifying group (3) has a polyglycerol chain, and hydrogen atoms of at least a portion of hydroxyl groups in the polyglycerol chain are substituted by monovalent organic groups.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a surface-modified nanodiamond and a method for producing a surface-modified nanodiamond. This application claims priority to Japanese Patent Application No. 2019-105065 filed in Japan on June 5, 2019, and the contents thereof are hereby incorporated by reference. Background Art

[0002] The fine material of known nanometer size has the new characteristic that can't show under the large size state.For example, nanometer diamond particle (=diamond particle of nanometer size) has the effect of mechanical strength, high refractive index, thermal conductivity, insulation, oxidation resistance, promotes the crystallization of resin etc.But, with regard to nanometer diamond particle, the ratio of its surface atoms is usually larger, therefore, the summation of the van der Waals force that can act between the surface atoms of adjacent particles is large, easily produces condensation (aggregation).In addition, under the situation of nanometer diamond particle, also can produce the phenomenon of so-called gathering (agglutination) of very firmly assembling because of the coulomb interaction between the crystal plane of adjacent microcrystal.Therefore, it is very difficult to make nanometer diamond particle dispersed in organic solvent, resin with the state of primary particle.For this reason, carried out by modifying the surface of nanometer diamond particle and giving dispersibility to nanometer diamond particle, thereby suppresses condensation.

[0003] For example, it is known that surface-modified nanodiamond particles having polyglycerol chains introduced on their surfaces have excellent solubility or dispersibility in water or polar organic solvents (see Patent Documents 1 and 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-248023

[0007] Patent Document 2: Japanese Patent Application Publication No. 2012-82103 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, generally speaking, the polarity of surface-modified nanodiamonds into which polyglycerol chains are introduced is extremely high, and therefore the dispersion medium that can be used is limited to highly polar solvents.

[0010] Therefore, an object of the present invention is to provide a surface-modified nanodiamond containing a polyglycerol chain having excellent dispersibility in a low-polarity solvent and a method for producing the same.

[0011] Solutions to the problem

[0012] The inventors of the present invention have conducted intensive research to achieve the above-mentioned purpose, and found that by blocking the polyglycerol chain ends in the polyglycerol chain-containing surface-modified nanodiamond with alcohol, isocyanate, or carboxylic acid chloride, a polyglycerol chain-containing surface-modified nanodiamond having excellent dispersibility in a low-polarity solvent can be obtained compared with a nanodiamond particle having a surface-modified group containing a polyglycerol chain whose hydroxyl end is not blocked. The present invention relates to a technical solution completed based on these findings.

[0013] That is, the present invention provides a surface-modified nanodiamond, comprising a nanodiamond particle and a surface-modifying group for surface-modifying the nanodiamond particle, wherein the surface-modifying group has a polyglycerol chain, and hydrogen atoms of at least a part of hydroxyl groups in the polyglycerol chain are substituted with a monovalent organic group.

[0014] The monovalent organic group is preferably a group represented by the following formula (1).

[0015] -XR (1)

[0016] [In the above formula (1), X represents a single bond, -C(=O)-, or -C(=O)-NH-. R represents a monovalent organic group, and the atom bonded to X is a carbon atom.]

[0017] The surface modifying group is preferably a polyglycerol chain-containing surface modifying group represented by the following formula (2).

[0018] -Y-(C3H6O2)p-(C3H5O2R 1 )q-OR 2 (1)

[0019] [In formula (1), p and q each represent the average degree of polymerization of the repeating units in parentheses, p is a value greater than or equal to 0, q is a value greater than or equal to 0, and p+q is a value greater than or equal to 1. 1 Represents a monovalent organic group. [-OR 2 ] indicates the end of the polyglycerol chain, R 2 represents a hydrogen atom or a monovalent organic group. 2 When Y is a hydrogen atom, q represents a value greater than 0. Y represents a single bond or a divalent group, and the bond arm extending to the left from Y is bonded to the nanodiamond particle.]

[0020] In the above formula (1), R preferably represents an alkyl group.

[0021] In the above formula (1), R preferably represents an alkyl group having 1 to 18 carbon atoms.

[0022] In the above formula (1), R preferably represents an ethyl group, a butyl group, or a hexyl group.

[0023] The surface modified nanodiamonds can be found in the FT-IR spectrum at 1510-1540 cm -1 Nearby and 1700~1730cm -1 There are absorption peaks near them.

[0024] The surface modified nanodiamonds can be found in the FT-IR spectrum at 1730-1750cm -1 There is an absorption peak near

[0025] The surface modified nanodiamonds can be 13 In the C-NMR spectrum, there are peaks in the vicinity of 5 to 45 ppm, in the vicinity of 60 to 85 ppm, and in the vicinity of 140 to 200 ppm.

[0026] The surface-modified nanodiamond is preferably dispersed in a Hildebrand solubility parameter (δ) of 10 (cal / cm 3 ) 1 / 2 The median particle size of at least one organic dispersion medium is 5 to 100 nm.

[0027] In addition, the present invention provides a method for producing a surface-modified nanodiamond, the method comprising: reacting a surface-modified nanodiamond (A) with one or more compounds selected from an alcohol (B1), an isocyanate (B2), and a carboxylic acid chloride (B3) to obtain the surface-modified nanodiamond, wherein the surface-modified nanodiamond (A) comprises nanodiamond particles and a surface-modifying group for surface-modifying the nanodiamond particles, wherein the surface-modifying group comprises a polyglycerol chain having a hydroxyl group.

[0028] Effects of the Invention

[0029] Compared with nanodiamond particles having a surface modification group comprising a polyglycerol chain whose hydroxyl terminal is not blocked, the surface modified nanodiamond of the present invention has excellent dispersibility in low polarity solvents. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is an enlarged schematic diagram showing an example of a surface-modified nanodiamond according to one embodiment of the present invention. The surface-modified ND [1] has a surface-modified group [3] having a polyglycerol chain [4] on the surface of an ND particle (part) [2].

[0031] Figure 2 This is a diagram showing the FT-IR spectrum of the surface-modified nanodiamond obtained in Example 1.

[0032] Figure 3This is a diagram showing the FT-IR spectrum of the surface-modified nanodiamond obtained in Example 2.

[0033] Figure 4 : is a figure which shows the FT-IR spectrum of the surface-modified nanodiamond obtained in Example 3.

[0034] Figure 5 3 is a diagram showing the FT-IR spectrum of the surface-modified nanodiamond obtained in Example 4.

[0035] Figure 6 3 is a diagram showing the FT-IR spectrum of the surface-modified nanodiamond obtained in Example 5.

[0036] Figure 7 This is a diagram showing the FT-IR spectrum of the nanodiamond obtained in Comparative Example 1.

[0037] Figure 8 The surface modified nanodiamond obtained in Example 2 is shown in FIG. 13 C-NMR spectrum.

[0038] Explanation of symbols

[0039] 1 Surface modified nanodiamond

[0040] 2 Nanodiamond particles

[0041] 3 Surface modification group (X)

[0042] 4 Polyglycerol chain DETAILED DESCRIPTION

[0043] [Surface modified nanodiamond]

[0044] The surface-modified nanodiamond (hereinafter, nanodiamond is sometimes referred to as "ND") of one embodiment of the present invention comprises nanodiamond particles and a surface-modifying group for surface-modifying the nanodiamond particles, wherein the surface-modifying group has a polyglycerol chain, and the hydrogen atoms of at least a part of the hydroxyl groups in the polyglycerol chain are replaced by a monovalent organic group. It should be noted that in this specification, the surface-modifying group having a polyglycerol chain and the hydrogen atoms of at least a part of the hydroxyl groups in the polyglycerol chain are sometimes referred to as a "surface-modifying group (X)". The surface-modified ND may have only one surface-modifying group (X), or may have two or more surface-modifying groups (X).

[0045] Figure 1This is an enlarged schematic diagram showing an example of a surface-modified ND according to one embodiment of the present invention, wherein the surface-modified ND [1] has a surface-modified group (surface-modified group (X)) [3] on the surface of the ND particle [2], and the surface-modified group (surface-modified group (X)) [3] has a polyglycerol chain [4] in which at least a portion of the hydrogen atoms of the hydroxyl group are replaced by a monovalent organic group. It should be noted that Figure 1 Y in the formula (2) is the same as Y in the formula (2) described later.

[0046] The ND particles constituting the surface-modified ND preferably include primary particles of nanodiamond. In addition, secondary particles formed by the agglomeration (aggregation) of the above-mentioned primary particles of several to several tens of degrees may also be included. In addition, on the surface of the surface-modified ND, in addition to the surface modification group (X), one or more other surface functional groups (e.g., amino, hydroxyl, carboxyl, etc.) may also be present.

[0047] The surface modification group (X) is a group having a polyglycerol chain and the hydrogen atoms of at least a portion of the hydroxyl groups in the polyglycerol chain are substituted by a monovalent organic group. That is, the monovalent organic group is bonded to the oxygen atom from the terminal hydroxyl group of the polyglycerol chain. In the surface modification group (X), the polyglycerol chain can be directly bonded to the ND particles or bonded via a divalent group. As the divalent group, the divalent group exemplified as Y in the formula (2) described later can be cited.

[0048] Examples of the monovalent organic group include substituted or unsubstituted hydrocarbon groups (monovalent hydrocarbon groups), substituted or unsubstituted heterocyclic groups (monovalent heterocyclic groups), groups formed by bonding two or more of them, and groups formed by bonding them to a bonding group. The above-mentioned bonded groups may be directly bonded or bonded together via a connecting group. Examples of the above-mentioned connecting groups include amino groups, ether bonds, ester bonds, phosphinic acid groups, thioether bonds, carbonyl groups, amide groups substituted by organic groups, carbamate bonds substituted by organic groups, imide bonds substituted by organic groups, thiocarbonyl groups, siloxane bonds, and groups formed by bonding two or more of them. In addition, the above-mentioned bonding group is a group bonded to the oxygen atom from the terminal hydroxyl group of the polyglycerol chain, and examples thereof include a group bonded to the above-mentioned oxygen atom to form an ester group, a group forming a carbamate bond (carbamoyl group, etc.), and the like.

[0049] Examples of the hydrocarbon group in the monovalent organic group include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a group in which two or more of these are bonded together.

[0050] Examples of the aliphatic hydrocarbon group include alkyl, alkenyl, and alkynyl groups. Examples of the alkyl group include methyl, ethyl, propyl, isopropyl, butyl, hexyl, octyl, isooctyl, decyl, and dodecyl groups.1-20 Alkyl (preferably C 1-10 Alkyl, more preferably C 1-4 Examples of the alkenyl group include vinyl, allyl, methallyl, 1-propenyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 5-hexenyl, and the like. 2-20 Alkenyl (preferably C 2-10 Alkenyl, more preferably C 2-4 Examples of the alkynyl group include C 2-(4-(4-nitro-1-yl)-2-yl) and C 2-(4-nitro-1-yl) groups. Examples of the alkynyl group include C 2-(4-nitro-1-yl) and C 2-(4-nitro-1-yl) groups. 2-20 Alkynyl (preferably C 2-10 Alkynyl, more preferably C 2-4 Alkynyl) etc.

[0051] Examples of the alicyclic hydrocarbon group include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cyclododecyl, and the like. 3-12 Cycloalkyl; cyclohexenyl, etc. 3-12 Cycloalkenyl; bicycloheptyl, bicycloheptenyl, etc. 4-15 Bridged cyclic hydrocarbon groups, etc.

[0052] Examples of the aromatic hydrocarbon group include C 6-14 Aryl (especially C 6-10 Aryl) etc.

[0053] Examples of the heterocyclic ring forming the heterocyclic group include aromatic heterocyclic rings and non-aromatic heterocyclic rings. Examples of such heterocyclic rings include 3- to 10-membered rings (preferably 4- to 6-membered rings) having carbon atoms and at least one hetero atom (e.g., oxygen atoms, sulfur atoms, nitrogen atoms, etc.) in the atoms constituting the ring, and condensed rings of these rings. Specifically, examples include heterocyclic rings containing oxygen atoms as heteroatoms (e.g., 3-membered rings such as oxirane rings; 4-membered rings such as oxetane rings; furan rings, tetrahydrofuran rings, Azole ring, iso oxazole ring, γ-butyrolactone ring and other 5-membered rings; 4-oxo-4H-pyran ring, tetrahydropyran ring, morpholine ring and other 6-membered rings; benzofuran ring, isobenzofuran ring, 4-oxo-4H-benzopyran ring, chroman ring, isochroman ring and other condensed rings; 3-oxatricyclic [4.3.1.1 4,8 ] undecane-2-one ring, 3-oxatricyclic [4.2.1.0 4,8] nonane-2-one ring and other bridged rings), heterocycles containing a sulfur atom as a heteroatom (for example, 5-membered rings such as thiophene ring, thiazole ring, isothiazole ring, thiadiazole ring, etc.; 6-membered rings such as 4-oxo-4H-thiopyran ring; condensed rings such as benzothiophene ring, etc.), heterocycles containing a nitrogen atom as a heteroatom (for example, 5-membered rings such as pyrrole ring, pyrrolidine ring, pyrazole ring, imidazole ring, triazole ring, etc.; 6-membered rings such as isocyanuric acid ring, pyridine ring, pyridazine ring, pyrimidine ring, pyrazine ring, piperidine ring, piperazine ring; condensed rings such as indole ring, dihydroindole ring, quinoline ring, acridine ring, naphthyridine ring, quinazoline ring, purine ring, etc.), etc.

[0054] Examples of the group formed by bonding an aliphatic hydrocarbon group to an alicyclic hydrocarbon group include cyclohexylmethyl and methylcyclohexyl. Examples of the group formed by bonding an aliphatic hydrocarbon group to an aromatic hydrocarbon group include benzyl, phenethyl, and the like. 7-18 Arylalkyl (especially C 7-10 Arylalkyl), cinnamyl, etc. 6-10 Aryl-C 2-6 C 1-4 Alkyl-substituted aryl, styryl, etc. 2-4 Alkenyl substituted aryl, etc.

[0055] Examples of the group in which two or more of the monovalent hydrocarbon groups and / or the monovalent heterocyclic groups are bonded via a linking group include a group in which the monovalent hydrocarbon group and / or the monovalent heterocyclic group is bonded to an alkoxy group, an alkenyloxy group, an alkynyloxy group, an aryloxy group, an aralkyloxy group, an acyloxy group, an alkylthio group, an alkenylthio group, an arylthio group, an aralkylthio group, an acyl group, an alkenylcarbonyl group, an arylcarbonyl group, an aralkylcarbonyl group, an alkoxycarbonyl group, an alkenyloxycarbonyl group, an aryloxycarbonyl group, an aralkyloxycarbonyl group, a dialkylamino group, an acylamino group, an oxetanyl-containing group, a carbamoyl group, or a group in which two or more of them are bonded.

[0056] The monovalent organic group may have a substituent. Examples of the substituent include halogen atoms such as fluorine, chlorine, bromine, and iodine atoms; hydroxyl groups; mercapto groups; carboxyl groups; amino groups; and oxo groups.

[0057] Among them, the monovalent organic group is preferably a group represented by the following formula (1).

[0058] -XR(1)

[0059] [In the above formula (1), X represents a single bond, -C(=O)-, or -C(=O)-NH-. R represents a monovalent organic group, and the atom bonded to X is a carbon atom.]

[0060] As the monovalent organic group in the above R, for example, substituted or unsubstituted hydrocarbon groups (monovalent hydrocarbon groups), substituted or unsubstituted heterocyclic groups (monovalent heterocyclic groups), groups formed by bonding two or more of them, etc. The above bonded groups may be directly bonded or bonded together via a connecting group. As the above connecting group, for example, amino groups, ether bonds, ester bonds, phosphinic acid groups, thioether bonds, carbonyl groups, amide groups substituted by organic groups, carbamate bonds substituted by organic groups, imide bonds substituted by organic groups, thiocarbonyl groups, siloxane bonds, groups formed by bonding two or more of them, etc. As the above monovalent hydrocarbon groups, monovalent heterocyclic groups, and groups formed by bonding two or more of them, the monovalent organic groups exemplified and described as the monovalent organic groups (monovalent organic groups bonded to the oxygen atoms from the terminal hydroxyl groups of the polyglycerol chain) in the above surface modification group (X) can be listed.

[0061] As the above R, a substituted or unsubstituted hydrocarbon group is preferred, an alkyl group is more preferred, an alkyl group having 1 to 18 carbon atoms is further preferred, an alkyl group having 1 to 6 carbon atoms is further preferred, and an ethyl group, a butyl group, or a hexyl group is particularly preferred. When there are a plurality of groups represented by the above formula (1) contained in the surface modification group (X), the R in the plurality of groups represented by the above formula (1) may be the same or different from each other.

[0062] The surface modification group (X) is preferably a polyglycerol chain-containing surface modification group represented by the following formula (2).

[0063] -Y-(C3H6O2)p-(C3H5O2R 1 )q-OR 2 (2)

[0064] [In formula (2), p and q each represent the average degree of polymerization of the repeating units in parentheses, p is a value greater than or equal to 0, q is a value greater than or equal to 0, and p+q is a value greater than or equal to 1. 1 Represents a monovalent organic group. [-OR 2 ] indicates the end of the polyglycerol chain, R 2 represents a hydrogen atom or a monovalent organic group. 2 When Y is a hydrogen atom, q represents a value greater than 0. Y represents a single bond or a divalent group, and the bond arm extending to the left from Y is bonded to the ND particle.]

[0065] [C3H6O2] marked with p in the above formula (2) has one or more structures represented by the following formulas (3) to (5).

[0066] -OCH2-CHOH-CH2- (3)

[0067] -OCH(CH2OH)-CH2- (4)

[0068] -OCH2-CH(CH2OH)- (5)

[0069] In the above formula (2), the q-marked [C3H5O2R 1 ] has one or more structures represented by the following formulae (6) to (8).

[0070] -OCH2-CH(OR 1 )-CH2- (6)

[0071] -OCH(CH2OR 1 )-CH2- (7)

[0072] -OCH2-CH(CH2OR 1 )- (8)

[0073] In the above formula (2), p and q represent the average polymerization degree (number average polymerization degree) of the repeating units in the brackets. p is a value greater than 0, q is a value greater than 1, and p+q represents a value greater than 1. 2 In the case of a hydrogen atom, q represents a value greater than 0. p+q is preferably 1 to 100, more preferably 2 to 40, and further preferably 3 to 30. When p+q is greater than 1, the steric hindrance between the surface modification groups becomes sufficient and is easily dispersed in the dispersion medium. When p+q is less than 100, the mutual entanglement between the surface modification groups is suppressed and is easily dispersed in the dispersion medium. Moreover, it is not easy to damage the characteristics as a nanodiamond material. It should be noted that [q / (p+q)] is preferably greater than 0.6 (for example, 0.8 to 1.0).

[0074] It should be noted that the above-mentioned average degree of polymerization is defined by the number of glycidyl units constituting the polyglycerol chain bonded to one surface functional group of the raw material nanodiamond, and the number of surface functional groups of the raw material nanodiamond can be determined by measuring the elemental analysis value of the raw material nanodiamond, measuring the acid value, or combining the two.

[0075] In the above formula (2), R 1 represents a monovalent organic group, preferably a group represented by the above formula (1). 1 The monovalent organic group in can be exemplified by the monovalent organic groups exemplified and described as the monovalent organic groups in the surface modification group (X) described above (monovalent organic groups bonded to the oxygen atom derived from the terminal hydroxyl group of the polyglycerol chain).

[0076] In the above formula (2), [-OR 2 ] indicates the end of the polyglycerol chain, R 2represents a hydrogen atom or a monovalent organic group, preferably represents a group represented by the above formula (1). 2 When it is a monovalent organic group, it is preferred that the plurality of R 2 Same as R 2 The monovalent organic group in can be exemplified by the monovalent organic groups exemplified and described as the monovalent organic groups in the surface modification group (X) described above (monovalent organic groups bonded to the oxygen atom derived from the terminal hydroxyl group of the polyglycerol chain).

[0077] In formula (2), Y represents a single bond or a divalent group, and the bond arm extending to the left from Y is bonded to the ND particle. Examples of the divalent group include amino (-NH-), ether bond (-O-), ester bond (-C(=O)O-), phosphine group (-PH(=O)O-), thioether bond (-S-), carbonyl group (-C(=O)-), amide group (-C(=O)-NH-), carbamate bond (-NH-C(=O)-O-), imide bond (-C(=O)-NH-C(=O)-), thiocarbonyl group (-C(=S)-), siloxane bond (-Si-O-), divalent hydrocarbon group, and groups formed by bonding two or more of them. Examples of the divalent hydrocarbon group include residues obtained by removing one hydrogen atom from the monovalent hydrocarbon group. In addition, the divalent group may also have a substituent. Examples of the substituent include the substituents exemplified and described as the substituents that the monovalent organic group may have.

[0078] Among them, Y is preferably a single bond, -NH-, -O-, -C(=O)O-, -PH(=O)O-, or -S-, and more preferably a single bond.

[0079] In the above formula (2), the bonding order of the structural unit marked with p and the structural unit marked with q is not particularly limited. That is, the oxygen atom bonded to Y in formula (2) may be an oxygen atom in the structural unit marked with p or an oxygen atom in the structural unit marked with q. 2 The carbon atom in the formula (2) to be bonded may be a carbon atom in a structural unit labeled with p or a carbon atom in a structural unit labeled with q. In addition, when one of p and q is 1 or more and the other is 2 or more, the bonding method of the structural unit labeled with p and the structural unit labeled with q may be any method selected from random, alternating, and block. In the case of having a plurality of structural units labeled with q, the plurality of R 1 They can be the same or different from each other. 1 In different cases, the bonding form of the structural units marked with q may be any of random, alternating and block bonding.

[0080] The mass ratio of ND in the above-mentioned surface-modified ND to the surface-modifying group (X) [ND / surface-modifying group (X)] is not particularly limited, and is preferably 0.5 to 1.0, and more preferably 0.6 to 0.8. When the above-mentioned mass ratio is 0.5 or more (especially 0.6 or more), it is not easy to damage the characteristics as a nanodiamond material. When the above-mentioned mass ratio is 1.0 or less (especially 0.8 or less), the degree of modification of the surface-modifying group (X) becomes sufficient, and the dispersibility in low-polarity solvents is more excellent. The above-mentioned mass ratio can be based on the weight reduction rate measured by thermogravimetric analysis, and the reduced weight is obtained and used as the mass of the surface-modifying group containing a polyglycerol chain.

[0081] In the first embodiment, it is preferred that in the FT-IR spectrum of the surface-modified ND, -1 Nearby and 1700~1730cm -1 It is estimated that the surface-modified ND having such absorption peaks corresponds to the surface-modified ND in which X in the above formula (1) is -C(=O)-NH-. It is estimated that the absorption peaks at 1510-1540cm -1 The absorption peaks near the NH stretching vibration are 1700-1730cm -1 The nearby absorption peak is derived from the stretching vibration of C═O. The above absorption peak may slightly vary depending on R and the like in the above formula (1).

[0082] In the second embodiment, it is preferred that in the FT-IR spectrum of the surface-modified ND, the -1 It is estimated that the surface-modified ND having such an absorption peak corresponds to the surface-modified ND in which X in the above formula (1) is -C(=O)-. It is estimated that the absorption peak at 1730-1750cm -1 The strong and sharp absorption peak in the vicinity is a peak derived from the stretching vibration of C═O. The above absorption peak may slightly vary depending on R and the like in the above formula (1).

[0083] Preferably, the surface-modified ND 13 In the C-NMR spectrum, there is a peak at about 140 to 200 ppm. It can be inferred that the surface-modified ND having such a peak corresponds to the surface-modified ND containing a carbonyl carbon such as -C(=O)- or -C(=O)-NH- in the above formula (1). 13 In the C-NMR spectrum, there is a peak at about 60 to 85 ppm. It is inferred that the peak is derived from polyglycerol. 13In the C-NMR spectrum, there is a peak at about 5 to 45 ppm. It can be estimated that the surface-modified ND having such a peak corresponds to the surface-modified ND in which R in the above formula (1) contains a monovalent aliphatic hydrocarbon group. The above peak may slightly vary depending on R in the above formula (1).

[0084] The surface-modified ND was dispersed in a liquid having an SP value of 10 (cal / cm2) so that the content ratio was 0.1 mass %. 3 ) 1 / 2 The median particle size (D50) of at least one of the following organic dispersion media is preferably 5 to 100 nm. That is, relative to at least one of the organic dispersion media that satisfies the above-mentioned SP value, the median particle size of the above-mentioned surface-modified ND in the dispersion medium is preferably within the above-mentioned range. The above-mentioned median particle size is more preferably 5 to 80 nm, and further preferably 5 to 50 nm. It should be noted that the above-mentioned SP value refers to the Hildebrand solubility parameter (δ) at 25°C. When the above-mentioned median particle size is within the above-mentioned range, the dispersibility in low-polarity solvents is better than that of nanodiamond particles having a surface-modified group comprising a polyglycerol chain whose hydroxyl end is not blocked.

[0085] Specifically, the median particle size can be determined as follows: the organic dispersion medium is added so that the surface-modified ND content reaches 0.1% by mass, stirred in an ultrasonic cleaner for 5 minutes, allowed to stand for 1 day, and then centrifuged at 20,000 × g for 10 minutes, and the surface-modified ND particles in the supernatant are measured to determine the median particle size.

[0086] The above SP value is 10 (cal / cm 3 ) 1 / 2 Examples of the organic dispersion medium include hexane (SP: 7.0), alkylbenzene (SP: 7.6), methyl isobutyl ketone (MIBK, SP: 8.4), toluene (SP: 8.8), tetrahydrofuran (SP: 9.1), ethyl acetate (SP: 9.1), methyl ethyl ketone (MEK, SP: 9.3), chloroform (SP: 9.3), polyol ester (SP: 9.6), dichloromethane (SP: 9.7), alkane (SP: 9.8), ethylene dichloride (SP: 9.8), acetone (SP: 10.0), poly-α-olefin (SP: about 6.0 to 8.0), mineral oil (SP: about 6.0 to 8.0), etc. The SP value is preferably 7 to 10.0 (cal / cm3)1 / 2, more preferably 7.3 to 9.9 (cal / cm3)1 / 2.

[0087] The surface-modified ND has excellent dispersibility in low-polarity solvents, and the polarity of the ND particles can be controlled by adjusting the branching structure of the polyglycerol chain or the length of the polyglycerol chain, thereby achieving dispersibility in various dispersion media and affinity for resins. Therefore, it can be used in engineering application fields such as CMP polishing agents, dresser materials, corrosion-resistant electrode plating materials for fuel cells, high-hardness surface coating forming materials such as cutting tools, and high heat-resistant / high thermal conductivity materials.

[0088] The particle size (D50) of the above-mentioned surface-modified ND is, for example, less than 400nm, preferably less than 300nm, more preferably less than 100nm, and further preferably less than 50nm. The lower limit of the particle size (D50) of the surface-modified ND is, for example, 5nm. In addition, the particle size (D90) is, for example, less than 500nm, preferably less than 180nm, and more preferably less than 170nm. The lower limit of the particle size (D90) of the surface-modified ND is, for example, 50nm. The smaller the particle size of the surface-modified ND, the higher the transparency will be obtained in the composite material described later, which is preferred from this aspect. It should be noted that the (average) particle size of the surface-modified ND can be measured by dynamic light scattering.

[0089] [Nanodiamond dispersion composition]

[0090] By dispersing the surface-modified ND in a dispersion medium, a nano-diamond dispersion composition (ND dispersion composition) including a dispersion medium and the surface-modified ND dispersed in the dispersion medium can be obtained.

[0091] The dispersion medium is a medium for dispersing the surface-modified ND, and examples thereof include water, an organic solvent, and an ionic liquid. The dispersion medium may be used alone or in combination of two or more.

[0092] Examples of the organic solvent include aliphatic hydrocarbons (particularly straight-chain saturated aliphatic hydrocarbons) such as hexane, heptane, and octane; aromatic hydrocarbons such as benzene, toluene, and xylene; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; aprotic polar solvents such as dimethylformamide (DMF), dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; alcohols such as methanol; halogenated hydrocarbons such as chloroform, dichloromethane, dichloroethane, carbon tetrachloride, chlorobenzene, and trifluoromethylbenzene; diethyl ether, diisopropyl ether, dimethoxyethane, tetrahydrofuran (THF), dimethoxyethane, and the like. Chain or cyclic ethers such as alkanes; esters such as ethyl acetate and butyl acetate; chain ketones such as methyl ethyl ketone (MEK) and methyl isobutyl ketone; nitriles such as acetonitrile, etc. Among them, cyclic ethers or chain ketones are preferred, and chain ketones are particularly preferred, from the perspective of particularly excellent dispersibility of the surface-modified ND.

[0093] The content ratio of the ND particles in the ND dispersion composition is not particularly limited, and is, for example, 0.1 ppm by mass to 10% by mass.

[0094] The content ratio of the above-mentioned ND particles can be calculated based on the absorbance at 350nm. It should be noted that, when the content ratio of the surface-modified ND is a low concentration (e.g., below 2000 mass ppm), the compound that is surface-modifying the ND particles can also be detected by high-frequency inductively coupled plasma emission spectrometry (ICP emission spectrometry), and the above-mentioned content ratio can be calculated based on the detected amount.

[0095] The content ratio of the dispersion medium in the ND dispersion composition is, for example, 90 to 99.9999% by mass, but the upper limit is 100% by mass.

[0096] The above-mentioned ND dispersion composition may be composed of only the above-mentioned surface-modified ND and the dispersion medium, or may contain other components. Examples of other components include surfactants, thickeners, coupling agents, dispersants, rust inhibitors, corrosion inhibitors, freezing point depressants, defoamers, anti-wear additives, preservatives, colorants, etc. The content ratio of the above-mentioned other components relative to the total amount of the above-mentioned ND dispersion composition is, for example, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 1% by mass or less. Therefore, the total content ratio of the above-mentioned surface-modified ND and the dispersion medium relative to the total amount of the above-mentioned ND dispersion composition is, for example, 70% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, more preferably 95% by mass or more, and particularly preferably 99% by mass or more.

[0097] The ND dispersion composition contains the surface-modified ND in a highly dispersed state. The average dispersed particle size (D50) of the ND particles in the ND dispersion composition is, for example, 100 nm or less, preferably 60 nm or less, more preferably 50 nm or less, and further preferably 30 nm or less. The lower limit of the average dispersed particle size of the ND particles is, for example, 5 nm.

[0098] The haze value of the ND dispersion composition is preferably 5 or less, more preferably 3 or less, and further preferably 1 or less. Since the surface-modified ND dispersion composition has excellent dispersibility, an ND dispersion composition having the above haze value can be obtained. The above haze value can be measured based on JIS K 7136.

[0099] The above-mentioned ND dispersion composition can be preferably used as an additive for a composite material that imparts the properties of fine ND particles to resins (e.g., heat or photocurable resins, thermoplastic resins, etc.) (e.g., mechanical strength, high refractive index, thermal conductivity, insulation, oxidation resistance, crystallization promotion, dendrite inhibition, etc.). Furthermore, the composition obtained by adding the above-mentioned ND dispersion composition to a resin can be preferably used as, for example: functional blending materials, thermal functional (heat resistance, heat storage, thermal conductivity, insulation, etc.) materials, photonics (organic EL elements, LEDs, liquid crystal displays, optical disks, etc.) materials, biological / biocompatible materials, coating materials, films (touch panels, hard coatings of various displays, heat insulation films, etc.) materials, sheet materials, screens (transmissive transparent screens, etc.) materials, fillers (heat dissipation fillers, fillers for improving mechanical properties, etc.) materials, heat-resistant plastic substrates (flexible display substrates, etc.) materials, lithium ion batteries, etc. The ND dispersion composition can also be used as a friction reducing agent or lubricant suitable for other medical applications, sliding parts of machine parts (for example, automobiles, airplanes, etc.), and the like.

[0100] [Method for producing surface-modified nanodiamond and nanodiamond dispersion composition]

[0101] The above-mentioned surface-modified ND can be produced by reacting a surface-modified ND (A) with one or more compounds selected from alcohol (B1), isocyanate (B2) and carboxylic acid chloride (B3), wherein the surface-modified ND (A) has ND particles and a surface-modifying group for surface-modifying the above-mentioned ND particles, and the surface-modifying group includes a polyglycerol chain having a hydroxyl group.

[0102] The surface modification group containing a polyglycerol chain (polyglycerol chain-containing surface modification group) has a hydroxyl group on the polyglycerol chain. The surface-modified ND having the surface modification group containing a polyglycerol chain (sometimes referred to as "surface-modified ND (A)") can be obtained by directly subjecting glycidol to ring-opening polymerization with ND particles. ND particles originally have carboxyl groups and hydroxyl groups generated during the manufacturing process, and by reacting these functional groups with glycidol, the surface of ND can be modified with a polyglycerol chain.

[0103] The reaction (ring-opening polymerization) of ND particles with glycidol can be carried out, for example, by adding glycidol and a catalyst to the ND particles in an inert gas atmosphere and heating to 50 to 100° C. As the catalyst, an acidic catalyst can be used, or a basic catalyst can be used. Examples of the acidic catalyst include boron trifluoride etherate, acetic acid, phosphoric acid, etc. Examples of the basic catalyst include triethylamine, pyridine, dimethylaminopyridine, triphenylphosphine, etc.

[0104] Regarding the ring-opening polymerization conditions of glycidol, reference may be made to J. Polym. Sci., Polym. Chem. Ed., Vol. 4, 1253 (1966) by SR Sandler et al., J. Polym. Sci., Polym. Chem. Ed., vol. 23, 915 (1985) by EJ Vanderberg, and Dendritic Macromolecules: Concepts, Syntheses, Perspectives, VCH, Weinheim (1996) by GR Newcome et al.

[0105] In addition, the surface-modified ND (A) can also be obtained by ring-opening polymerization of glycidol with ND particles having functional groups containing active hydrogen introduced on the surface. The functional group containing active hydrogen is not particularly limited, and examples thereof include amino, hydroxyl, carboxyl, mercapto (thiol), phosphinate, and the like. As a method for introducing the above-mentioned functional groups containing active hydrogen into ND particles, reference can be made to Japanese Patent Publication No. 2012-82103, Japanese Patent Publication No. 2010-248023, and the like. The ring-opening polymerization of glycidol with respect to the above-mentioned ND particles having functional groups containing active hydrogen introduced on the surface can be carried out in the same manner as the ring-opening polymerization of glycidol with respect to the above-mentioned ND particles.

[0106] In addition, when alcohol (B1) is used, the surface modified ND is obtained by reacting the surface modified ND (A) with alcohol (B1) to form an ether bond by dehydration condensation. In the case of using isocyanate (B2), the surface modified ND is obtained by reacting the surface modified ND (A) with isocyanate (B2), and the isocyanate group in the isocyanate is added to the hydroxyl group to form a carbamate bond (carbamoyl group). In addition, when carboxylic acid chloride (B3) is used, the surface modified ND is obtained by reacting the surface modified ND (A) with carboxylic acid chloride (B3) to form an ester bond.

[0107] Alcohol (B1), isocyanate (B2), and carboxylic acid chloride (B3) can be appropriately selected according to the surface modified ND to be obtained. The organic group bonded to the hydroxyl group in the alcohol (B1), the organic group on the nitrogen atom in the isocyanate (B2), and the organic group bonded to the carbonyl group in the carboxylic acid chloride (B3) are respectively equivalent to R in the above formula (1), and for example, the monovalent organic group exemplified and explained as the above R can be cited. Alcohol (B1), isocyanate (B2), and carboxylic acid chloride (B3) can be used alone or in combination of two or more.

[0108] As alcohol (B1), C 1-18Alcohol, more preferably ethanol, n-butanol, n-hexanol.

[0109] As for the isocyanate (B2), alkyl isocyanate is preferred, and isocyanate C is more preferred. 1-18 The alkyl ester is more preferably ethyl isocyanate, n-butyl isocyanate, or n-hexyl isocyanate.

[0110] As for the carboxylic acid chloride (B3), the acid chloride is preferred, and the number of carbon atoms in the acyl group is preferably C 1-19 Alkyl, more preferably valeryl chloride.

[0111] The reaction with the above-mentioned alcohol, the above-mentioned isocyanate, or the above-mentioned carboxylic acid chloride can be carried out in a solvent. As the above-mentioned solvent, the above-mentioned organic solvent can be listed. The above-mentioned reaction can be carried out, for example, by adding a catalyst to the ND particles in an inert gas atmosphere and stirring at room temperature. As the catalyst, a basic catalyst is preferably used. As the above-mentioned basic catalyst, tertiary amines such as triethylamine, pyridine, dimethylaminopyridine, and triphenylphosphine can be listed. It should be noted that, when the basic catalyst is a liquid, a basic catalyst can also be used as a reaction solvent.

[0112] The ratio of the surface modified ND (A) to the alcohol (B1), isocyanate (B2), and / or carboxylic acid chloride (B3) provided for the reaction (former: latter, mass ratio) is, for example, 2: 1 to 1: 80. In addition, the concentration of the surface modified ND (A) in the solvent is, for example, 0.5 to 10% by mass, and the concentration of the alcohol (B1), isocyanate (B2), and / or carboxylic acid chloride (B3) in the solvent is, for example, 5 to 60% by mass.

[0113] The reaction time of the surface-modified ND (A) with the alcohol (B1), the isocyanate (B2), and / or the carboxylic acid chloride (B3) is, for example, 4 to 24 hours.

[0114] As described above, the surface modified ND and the ND dispersion composition in which the surface modified ND is dispersed in a dispersion medium can be obtained. It should be noted that, when ND aggregates remain after the reaction, it is preferred to collect the supernatant after the reaction is left to stand and use it as the ND dispersion composition. In addition, when a solvent that is beneficial to the reaction is used in the reaction of the surface modified ND (A) with the alcohol (B1), isocyanate (B2), and / or carboxylic acid chloride (B3), the ND dispersion composition can be produced by distilling off the dispersion medium in the dispersion using an evaporator or the like after temporarily obtaining the dispersion of the surface modified ND particles, and then mixing a new dispersion medium and stirring, that is, by exchanging the solvent.

[0115] It should be noted that, as ND particles before surface modification, for example, detonation ND (i.e., ND generated by detonation), high temperature and high pressure ND (i.e., ND generated by high temperature and high pressure) can be used. Among them, detonation ND is preferred from the aspect that the dispersibility in the dispersion medium is more excellent, i.e., the particle size of the primary particles is a single-digit nanometer level.

[0116] The detonation ND includes air-cooled detonation ND (i.e., ND generated by air-cooled detonation) and water-cooled detonation ND (i.e., ND generated by water-cooled detonation). Among them, the air-cooled detonation ND is more preferable than the water-cooled detonation ND in that the primary particles are smaller.

[0117] The detonation may be carried out in an atmospheric atmosphere or in an inert gas atmosphere such as a nitrogen atmosphere, an argon atmosphere, or a carbon dioxide atmosphere.

[0118] An example of a method for producing ND particles used in the above-mentioned production method will be described, but the ND particles used are not limited to those obtained by the following production method.

[0119] (Generation process)

[0120] The material with electric detonators on the formed explosive is placed inside a pressure-resistant container for detonation, and the container is sealed in a state where atmospheric pressure gas and the explosive coexist in the container. The container is made of iron, for example, and the volume of the container is, for example, 0.5 to 40 m 3 As an explosive, a mixture of trinitrotoluene (TNT) and cyclotrimethylene trinitramine, namely RDX, can be used. The mass ratio of TNT to RDX (TNT / RDX) is, for example, in the range of 40 / 60 to 60 / 40.

[0121] In the generation process, the electric detonator is then detonated to cause the explosive to explode in the container. Detonation refers to the movement of the flame surface that reacts in the explosion accompanied by a chemical reaction at a high speed exceeding the speed of sound. During the detonation, the carbon released by the partial incomplete combustion of the explosive is used as a raw material, and ND particles are generated by the pressure and energy of the shock wave generated in the explosion. For the generated ND particles, adjacent primary particles or crystallites will be very strongly aggregated and formed into aggregates due to the Coulomb interaction between crystal planes in addition to the van der Waals force.

[0122] In the generation process, then, the container and its interior are cooled by naturally cooling at room temperature for about 24 hours. After the natural cooling, the ND particle crude product (including the aggregates and smoke of the ND particles generated as described above) attached to the inner wall of the container is scraped with a spatula to recover the ND particle crude product. By the method as described above, a crude product of ND particles (ND particle crude product) can be obtained. In addition, by performing the nanodiamond generation process as described above for a necessary number of times, a desired amount of ND particle crude product can be obtained.

[0123] (Acid treatment process)

[0124] In the acid treatment process, for example, a strong acid is allowed to act on the ND particle crude product as a raw material in an aqueous solvent to remove metal oxides. The ND particle crude product obtained by the detonation method is likely to contain metal oxides, which are oxides of Fe, Co, Ni, etc. from the container used in the detonation method. For example, by allowing a strong acid to act in an aqueous solvent, the metal oxide can be dissolved / removed (acid treatment) from the ND particle crude product. As the strong acid used in the acid treatment, an inorganic acid is preferred, for example, hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, and aqua regia can be listed. The above-mentioned strong acid can be used alone or in combination. The concentration of the strong acid used in the acid treatment is, for example, 1 to 50% by mass. The acid treatment temperature is, for example, 70 to 150°C. The acid treatment time is, for example, 0.1 to 24 hours. In addition, the acid treatment can be carried out under reduced pressure, normal pressure, or under pressure. After such an acid treatment, it is preferred to wash the solid component (including nanodiamond aggregates) with water by, for example, decantation. The solid component is preferably washed with water by decantation repeatedly until the pH of the precipitate reaches, for example, 2 to 3. When the content of metal oxide in the crude ND particles obtained by the detonation method is small, the acid treatment described above may be omitted.

[0125] (Oxidation treatment process)

[0126] The oxidation treatment process is a process for removing graphite from the ND particle crude product using an oxidant. The ND particle crude product obtained by the detonation method contains graphite, but the graphite originates from the carbon that is freed from the carbon that is partially incompletely burned using explosives and does not form ND particle crystals. By allowing the oxidant to act on the ND particle crude product in an aqueous solvent, graphite can be removed from the ND particle crude product. In addition, by allowing the oxidant to act, oxygen-containing groups such as carboxyl and hydroxyl groups can be introduced into the surface of the ND particles.

[0127] As the oxidizing agent used in the oxidation treatment, for example, chromic acid, chromic anhydride, dichromic acid, permanganic acid, perchloric acid, nitric acid, mixtures thereof, mixed acids of at least one acid selected from these acids and other acids (such as sulfuric acid), and salts thereof can be cited. Among them, mixed acids (particularly mixed acids of sulfuric acid and nitric acid) are preferably used from the viewpoints of excellent environmental performance and excellent graphite oxidation / removal effects.

[0128] From the perspective that graphite can be effectively oxidized and removed at a temperature of, for example, 130°C or more (particularly preferably 150°C or more. The upper limit is, for example, 200°C) even at a pressure near normal pressure (for example, 0.5 to 2 atm), the mixing ratio of sulfuric acid to nitric acid in the mixed acid (former / latter; mass ratio) is preferably, for example, 60 / 40 to 95 / 5. The lower limit is preferably 65 / 35, and more preferably 70 / 30. In addition, the upper limit is preferably 90 / 10, more preferably 85 / 15, and most preferably 80 / 20. When the above mixing ratio is 60 / 40 or more, the content of sulfuric acid having a high boiling point is high, so that at a pressure near normal pressure, the reaction temperature reaches, for example, 120°C or more, and there is a tendency for the removal efficiency of graphite to be improved. When the above mixing ratio is 95 / 5 or less, the content of nitric acid that significantly contributes to the oxidation of graphite increases, so there is a tendency for the removal efficiency of graphite to be improved.

[0129] The amount of the oxidant (especially the mixed acid) used is, for example, 10 to 50 parts by mass, preferably 15 to 40 parts by mass, and more preferably 20 to 40 parts by mass, relative to 1 part by mass of the crude ND particles. In addition, the amount of sulfuric acid in the mixed acid is, for example, 5 to 48 parts by mass, preferably 10 to 35 parts by mass, and more preferably 15 to 30 parts by mass, relative to 1 part by mass of the crude ND particles. In addition, the amount of nitric acid in the mixed acid is, for example, 2 to 20 parts by mass, preferably 4 to 10 parts by mass, and more preferably 5 to 8 parts by mass, relative to 1 part by mass of the crude ND particles.

[0130] In addition, when the mixed acid is used as the oxidant, a catalyst can be used at the same time as the mixed acid. By using a catalyst, the removal efficiency of graphite can be further improved. Examples of the catalyst include copper (II) carbonate. The amount of the catalyst used is, for example, about 0.01 to 10 parts by mass relative to 100 parts by mass of the crude ND particle product.

[0131] The oxidation treatment temperature is, for example, 100 to 200° C. The oxidation treatment time is, for example, 1 to 24 hours. The oxidation treatment can be performed under reduced pressure, normal pressure, or increased pressure.

[0132] (Alkaline Hydrogen Peroxide Treatment Process)

[0133] In the case where there are still metal oxides that have not been completely removed in the ND particles after the above-mentioned acid treatment process, the primary particles will form aggregates (secondary particles) in which very strong interactions occur between the primary particles and aggregate together. In such a case, an alkali and hydrogen peroxide can be allowed to act on the ND particles in an aqueous solvent. In this way, the metal oxides remaining in the ND particles can be removed, and the separation of the primary particles from the aggregates can be promoted. As the alkali used for this treatment, for example: sodium hydroxide, ammonia, potassium hydroxide, etc. can be listed. In the alkaline hydrogen peroxide treatment, the concentration of the alkali is, for example, 0.1 to 10% by mass, the concentration of hydrogen peroxide is, for example, 1 to 15% by mass, the treatment temperature is, for example, 40 to 100°C, and the treatment time is, for example, 0.5 to 5 hours. In addition, the alkaline hydrogen peroxide treatment can be carried out under reduced pressure, under normal pressure, or under pressure.

[0134] It is preferred that after the oxidation treatment step or the alkali hydrogen peroxide treatment step, the supernatant is removed by, for example, decantation. In addition, during decantation, it is preferred to wash the solid content with water. The supernatant obtained by the initial water washing may be colored, but it is preferred that the solid content be washed with water repeatedly until the supernatant becomes transparent under naked eye observation.

[0135] (Crushing process)

[0136] As required, the ND particles may also be subjected to a crushing treatment. For example, a high shear mixer, a high shear mixer, a homogenizer, a ball mill, a bead mill, a high pressure homogenizer, an ultrasonic homogenizer, a colloid mill, etc. may be used in the crushing treatment. It should be noted that the crushing treatment may be carried out in a wet manner (for example, a crushing treatment in a state of being suspended in water, etc.) or in a dry manner. In the case of a dry manner, it is preferred to provide a drying step before the crushing treatment. In addition, in the case of an oxidation treatment or a hydrogenation treatment, a crushing treatment step may be carried out after these treatments.

[0137] (Drying process)

[0138] It is preferred to provide a drying step after the alkaline hydrogen peroxide treatment step. For example, after evaporating the liquid component from the ND particle-containing solution obtained through the alkaline hydrogen peroxide treatment step using a spray dryer, an evaporator, etc., the residual solid component produced thereby is dried by heating and drying in a drying oven. The heating and drying temperature is, for example, 40 to 150° C. By undergoing such a drying step, ND particles can be obtained.

[0139] In addition, as required, the ND particles may be subjected to oxidation treatment (e.g., oxygen oxidation) or reduction treatment (e.g., hydrogenation treatment) in the gas phase. By performing oxidation treatment in the gas phase, ND particles having a large number of C=O groups on the surface may be obtained. In addition, by performing reduction treatment in the gas phase, ND particles having a large number of CH groups on the surface may be obtained.

[0140] Each embodiment disclosed in this specification can be combined with any other feature disclosed in this specification. Each scheme in each embodiment and their combination are examples, and the scheme can be appropriately added, omitted, replaced, and other changes can be made within the scope of the subject matter of the present invention. In addition, the inventions disclosed in this disclosure are not limited to the embodiments or the following examples, but are only limited to the claims.

[0141] Example

[0142] Hereinafter, one embodiment of the present invention will be described in more detail based on examples.

[0143] Example 1

[0144] The surface-modified ND particles and the dispersion composition were produced through the following steps.

[0145] (Preparation of surface-modified ND particles)

[0146] First, the ND generation process using the detonation method is carried out. In this process, first, the material with the electric detonator installed on the molded explosive is placed inside the pressure-resistant container for detonation, and the container is sealed. The container is made of iron and has a capacity of 15m 3 . As an explosive, 0.50 kg of a mixture of TNT and RDX was used. The mass ratio of TNT to RDX in the explosive (TNT / RDX) was 50 / 50. Next, the electric detonator was detonated to detonate the explosive in the container (production of ND by the detonation method). Next, the container and its interior were cooled by leaving it at room temperature for 24 hours. After the natural cooling, the ND crude product (including aggregates of ND particles and smoke generated by the above-mentioned detonation method) attached to the inner wall of the container was scraped off with a spatula, and the ND crude product was recovered.

[0147] Next, the ND crude product obtained by performing the above-mentioned generation process multiple times is subjected to an acid treatment process. Specifically, the slurry obtained by adding 6L of 10% by mass hydrochloric acid to 200g of the ND crude product is heated under reflux at normal pressure for 1 hour. The heating temperature in the acid treatment is 85-100°C. Then, after cooling, the solid component (including ND aggregates and smoke) is washed with water by decantation. The washing of the solid component based on decantation is repeated until the pH of the precipitate reaches from the lower pH side to 2.

[0148] Next, an oxidation treatment process is performed. Specifically, after adding 6L of 98 mass % sulfuric acid and 1L of 69 mass % nitric acid to the precipitate (including ND aggregates) obtained by decantation after acid treatment to prepare a slurry, the slurry was heated for 48 hours under reflux under normal pressure conditions. The heating temperature in the oxidation treatment is 140 to 160°C. Then, after cooling, the solid component (including ND aggregates) was washed with water by decantation. When the supernatant of the initial washing was colored, the washing of the solid component by decantation was repeated until the supernatant became transparent under naked eye observation.

[0149] Next, the precipitate liquid (liquid containing ND aggregates) obtained by the water washing process was subjected to a drying process to obtain a dry powder (ND aggregates). As a drying process method in the drying process, evaporation drying and solidification using an evaporator was used.

[0150] Next, 4.5 g of the dry powder (ND aggregate) obtained by the above-mentioned drying process was placed in the furnace core tube of an atmosphere furnace (trade name "atmosphere tube furnace KTF045N1", manufactured by Koyo Thermo System Co., Ltd.), and nitrogen was continuously circulated in the furnace core tube at a flow rate of 1 L / min for 30 minutes, and then the circulating gas was switched from nitrogen to a mixed gas of oxygen and nitrogen, and the mixed gas was continuously circulated in the furnace core tube at a flow rate of 1 L / min. The oxygen concentration in the mixed gas was 4% by volume. After switching to the mixed gas, the temperature in the furnace was raised to a heating setting temperature of 400°C. For the heating rate, it was set to 10°C / min until it reached 380°C, which was 20°C lower than the heating setting temperature, and then it was set to 1°C / min from 380°C to 400°C. Next, the temperature condition in the furnace was maintained at 400°C, and the ND powder in the furnace was subjected to oxygen oxidation treatment. The treatment time was set to 3 hours.

[0151] Next, the above-mentioned atmosphere furnace was continued to be used for the hydrogenation process. Specifically, for an atmosphere furnace in which ND powder after the oxygen oxidation process is configured, nitrogen is continuously circulated at a flow rate of 1L / min for 30 minutes, and then the circulating gas is switched from nitrogen to a mixed gas of hydrogen and nitrogen, and the mixed gas is continuously circulated in the furnace core tube at a flow rate of 1L / min. The hydrogen concentration in the mixed gas is 2% by volume. After switching to the mixed gas, the temperature in the furnace is raised to the heating set temperature of 600°C. The heating rate is set to 10°C / min. Then, the temperature condition in the furnace is maintained at 600°C, and the ND powder in the furnace is hydrogenated. The treatment time is set to 5 hours. As described above, the ND powder after hydrogenation is obtained.

[0152] Next, a crushing process was performed. Specifically, first, 0.9 g of the ND powder after the hydrogenation process and 29.1 ml of pure water were added to a 50 ml sample bottle and mixed to obtain about 30 ml of slurry. After adjusting the pH to 4 using 1 equivalent of hydrochloric acid, the slurry was subjected to ultrasonic treatment. In the ultrasonic treatment, an ultrasonic irradiator (trade name "ultrasonic cleaning machine AS-3", manufactured by AS ONE) was used to irradiate the slurry with ultrasonic waves for 2 hours. Then, a bead milling device (trade name "parallel four-cylinder sand mill LSG-4U-2L type", manufactured by IMEX Co., Ltd.) was used to perform bead milling. Specifically, 30 ml of the slurry after ultrasonic irradiation and zirconia beads with a diameter of 30 μm were put into a vessel (Vessel) (manufactured by IMEX Co., Ltd.) as a grinding container relative to 100 ml and sealed, and the device was driven to perform bead milling. In this bead mill, the amount of zirconium oxide beads introduced is, for example, 33% by volume relative to the volume of the grinding container, the rotation speed of the grinding container is 2570 rpm, and the grinding time is 2 hours.

[0153] Next, for the slurry that has passed through the above-mentioned crushing process, centrifugal separation (classification operation) is carried out using a centrifugal separation device. The centrifugal force in the centrifugal separation is set to 20000×g, and the centrifugal time is set to 10 minutes. Next, the supernatant 10mL of the ND solution containing after the centrifugal separation is recovered. In this way, an ND dispersion liquid dispersed with nano diamonds in pure water is obtained. About this nano diamond dispersion liquid, the solid content concentration is 2.1% by mass %, and the pH is 5.40. The median particle size (particle size D50) of the ND dispersion liquid thus obtained is 35.8nm.

[0154] Next, the ND particle aqueous dispersion obtained by the above-mentioned crushing process was dried using an evaporator to obtain a black dry powder. The obtained dry powder (100 mg) was added to 12 mL of glycidol placed in a glass reactor and dissolved by ultrasonic treatment for 2 hours at room temperature using an ultrasonic cleaner (trade name "BRANSON2510", manufactured by Marshall Scientific). It was reacted at 140 ° C for 20 hours while stirring in a nitrogen atmosphere. After the reaction mixture was cooled, 120 mL of methanol was added and ultrasonic treatment was performed, and then centrifuged at 50400 × g for 2 hours to obtain a precipitate. For the precipitate, 120 mL of methanol was added, and the washing-centrifugation process was repeated 5 times in the same way. Finally, the precipitate was dialyzed with pure water using a dialysis membrane (Spectra / Prodialysis membrane, MWCO: 12-14 kDa), and the residual methanol was replaced with water and freeze-dried to obtain a gray powder of hydrophilic ND particles (PG-ND particles) modified with polyglycerol. The ratio of ND particles to surface modification groups was measured by TG-DTA thermal analysis, and the result was that ND particles: surface modification groups = 1:1.39.

[0155] Pyridine was added to the PG-ND gray powder, and the concentration was adjusted to 4 g / L based on the mass of the ND particles, to obtain a PG-ND particle pyridine dispersion. 4 g of ethyl isocyanate was added to 20 ml of the obtained PG-ND particle pyridine dispersion, and stirred at room temperature for 30 minutes. Next, 40 ml of hexane was added, and centrifuged at 20,000 × g for 10 minutes to obtain a precipitate. The washing operation was repeated 3 times, and after removing the pyridine, it was left to stand at 50°C in a vacuum dryer for 24 hours, thereby obtaining a dry solid component. As described above, a surface-modified nanodiamond in which at least a portion of the hydroxyl ends of the polyglycerol chain were blocked by ethyl isocyanate was obtained. The mass ratio [ND / surface modification group containing polyglycerol chain] of the obtained surface-modified nanodiamond particles obtained by thermogravimetric analysis was 0.60.

[0156] Relative to the above-mentioned dry solid component that obtains, add tetrahydrofuran (THF) in the mode that makes ND contain ratio reach 0.1 quality %, in ultrasonic cleaning apparatus, carry out 5 minutes stirring, the result that the outward appearance after leaving standstill 1 day is observed, can confirm that has kept good dispersion.Carried out 10 minutes centrifugation with 20000 × g, the median particle diameter (particle diameter D50) of the surface modified nano-diamond particle of the supernatant that obtains is 34nm.The situation that has used methyl alcohol to replace tetrahydrofuran (THF) has been carried out same operation, and the result can confirm that has kept good dispersion.On the other hand, the situation that has used ultrapure water to replace tetrahydrofuran (THF) has been carried out same operation, and the result confirms that nano-diamond gathers and precipitates.

[0157] Example 2

[0158] Except that 5.6 g of n-butyl isocyanate was used instead of 4 g of ethyl isocyanate, a dry solid content (surface-modified nanodiamonds in which at least a portion of the hydroxyl ends of the polyglycerol chains were blocked by n-butyl isocyanate) was obtained in the same manner as in Example 1. The mass ratio [ND / surface-modified groups containing polyglycerol chains] of the obtained surface-modified nanodiamond particles obtained by thermogravimetric analysis was 0.74.

[0159] Relative to the above-mentioned dry solid component that obtains, add tetrahydrofuran (THF) in the mode that makes ND contain ratio reach 0.1 quality %, in ultrasonic cleaning apparatus, carry out 5 minutes stirring, the result that the outward appearance after leaving standstill 1 day is observed, can confirm that has kept good dispersion.Carried out 10 minutes centrifugation with 20000 × g, the median particle diameter (particle diameter D50) of the surface modified nano-diamond particle of the supernatant that obtains is 38nm.The situation that has used methyl alcohol to replace tetrahydrofuran (THF) has been carried out same operation, and the result can confirm that has kept good dispersion.On the other hand, the situation that has used ultrapure water to replace tetrahydrofuran (THF) has been carried out same operation, and the result confirms that nano-diamond gathers and precipitates.

[0160] Example 3

[0161] Except that 7.16 g of n-hexyl isocyanate was used instead of ethyl isocyanate, a dry solid content (surface-modified nanodiamonds in which at least a portion of the hydroxyl ends of the polyglycerol chains were blocked by n-hexyl isocyanate) was obtained in the same manner as in Example 1. The mass ratio [ND / surface-modified groups containing polyglycerol chains] of the obtained surface-modified nanodiamond particles obtained by thermogravimetric analysis was 0.62.

[0162] Relative to the above-mentioned dry solid component that obtains, add tetrahydrofuran (THF) in the mode that makes ND contain ratio reach 0.1 quality %, in ultrasonic cleaning apparatus, carry out 5 minutes stirring, the result that the outward appearance after leaving standstill 1 day is observed, can confirm that has kept good dispersion state.Carried out 10 minutes centrifugation with 20000 × g, the median particle diameter (particle diameter D50) of the surface modified nano-diamond particle of the supernatant that obtains is 42nm.The situation that toluene has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result can confirm that has kept good dispersion state.On the other hand, the situation that methyl alcohol has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result confirms that nano-diamond gathers and precipitates.In addition, the situation that ultrapure water has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result confirms that nano-diamond gathers and precipitates.

[0163] Example 4

[0164] Pyridine was added to the PG-ND gray powder obtained in Example 1, and the concentration was adjusted to 2 g / L based on the mass of the ND particles, and a PG-ND particle pyridine dispersion was obtained. 4.8 g of valeryl chloride was added to 40 ml of the obtained PG-ND particle pyridine dispersion, and stirred at 60 ° C for 24 hours. Next, after adding 80 ml of ultrapure water, centrifugation was performed at 6000 × g for 5 minutes, and after removing the supernatant, 40 ml of methanol was added and stirred, and then centrifugation was performed at 20000 × g for 10 minutes, and the precipitate was washed. Repeat this washing operation 3 times, remove pyridine, and stand at 50 ° C in a vacuum dryer for 24 hours, thereby obtaining a dry solid component. As described above, a surface-modified nanodiamond in which at least a portion of the hydroxyl ends of the polyglycerol chain are blocked by carboxylic acid esters can be obtained. The mass ratio [ND / surface modification group containing polyglycerol chain] of the obtained surface-modified nanodiamond particles obtained by thermogravimetric analysis is 0.61.

[0165] Relative to the above-mentioned dry solid component that obtains, add tetrahydrofuran (THF) in the mode that makes ND contain ratio reach 0.1 quality %, in ultrasonic cleaning apparatus, carry out 5 minutes stirring, the result that the outward appearance after leaving standstill 1 day is observed, can confirm that has kept good dispersion state.Carried out 10 minutes centrifugation with 20000 × g, the median particle diameter (particle diameter D50) of the surface modified nano-diamond particle of the supernatant that obtains is 38nm.The situation that toluene has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result can confirm that has kept good dispersion state.On the other hand, the situation that methyl alcohol has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result confirms that nano-diamond gathers and precipitates.In addition, the situation that ultrapure water has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result confirms that nano-diamond gathers and precipitates.

[0166] Example 5

[0167] Pyridine was added to the PG-ND gray powder obtained in Example 1, and the concentration was adjusted to 2 g / L based on the mass of the ND particles, and a PG-ND particle pyridine dispersion was obtained. 5.5 g of heptanoyl chloride was added to 40 ml of the obtained PG-ND particle pyridine dispersion, and stirred at 60 ° C for 24 hours. Next, after adding 80 ml of methanol, centrifugation was performed at 6000 × g for 5 minutes, and after removing the supernatant, 40 ml of methanol was added and stirred, and then centrifugation was performed at 20000 × g for 10 minutes, and the precipitate was washed. Repeat this washing operation 3 times, remove pyridine, and stand at 50 ° C in a vacuum dryer for 24 hours, thereby obtaining a dry solid component. As described above, a surface-modified nanodiamond in which at least a portion of the hydroxyl ends of the polyglycerol chain are blocked by carboxylic acid esters can be obtained. The mass ratio [ND / surface modification group containing polyglycerol chain] of the obtained surface-modified nanodiamond particles obtained by thermogravimetric analysis is 0.68.

[0168] Relative to the above-mentioned dry solid component obtained, add tetrahydrofuran (THF) in the mode that makes ND contain ratio reach 0.1 quality %, carry out stirring for 5 minutes in ultrasonic cleaning device, the result that the outward appearance after standing for 1 day is observed, can confirm that good dispersion is maintained.Carry out 10 minutes centrifugation with 20000 × g, the median particle diameter (particle diameter D50) of the surface modified nano-diamond particle of the supernatant obtained is 27.5nm.The situation that toluene has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result can confirm that good dispersion is maintained.In addition, the situation that hexane has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result can confirm that good dispersion is maintained.On the other hand, the situation that methyl alcohol has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result confirms that nano-diamond gathers and precipitates.In addition, the situation that ultrapure water has been used to replace tetrahydrofuran (THF) has been carried out the same operation, and the result confirms that nano-diamond gathers and precipitates.

[0169] Comparative Example 1

[0170] Add tetrahydrofuran (THF) to PG-ND gray powder so that ND solids reaches 0.1% by mass, then, stir 5 minutes in ultrasonic cleaning apparatus, observe outward appearance after standing for 1 day, the result confirms that nano-diamond gathers and precipitates.On the other hand, the situation that methyl alcohol is used to replace tetrahydrofuran (THF) is also carried out the same operation, and nano-diamond keeps good dispersion state as a result.In addition, the situation that ultrapure water is used to replace tetrahydrofuran (THF) is also carried out the same operation, and nano-diamond keeps good dispersion state as a result.

[0171] <Particle size D50>

[0172] The median particle size (particle size D50) of the ND particles in the ND dispersion composition of the embodiment obtained as described above was measured according to the particle size distribution of the nanodiamond obtained by the dynamic light scattering method. For the above-mentioned particle size distribution, a device manufactured by Malvern (trade name "Zetasizer Nano ZS") was specifically used and the particle size distribution of the nanodiamond was measured by the dynamic light scattering method (non-contact backscattering method).

[0173] <Thermogravimetric analysis>

[0174] The sample (about 3 mg) was heated at a heating rate of 20°C / min in an air atmosphere using a TG / DTA (thermogravimetric / differential thermal analysis) apparatus (trade name "EXSTAR 6300", manufactured by SII NanoTechnology) to measure the weight loss. Alumina was used as a reference substance.

[0175] <FT-IR analysis>

[0176] The surface-modified nanodiamonds obtained in Examples 1 to 5 and Comparative Example 1 were measured by FT-IR using a Fourier transform infrared spectrometer "IRTracer" (manufactured by Shimadzu Corporation) equipped with a heated vacuum stirring reflection "Heat Chamber Type-1000°C" (manufactured by ST Japan Corporation). It should be noted that in order to remove the adsorbed water of the ND particles, the vacuum was 2×10 -3 After heating at 150° C. for 10 minutes under Pa, FT-IR measurement was performed.

[0177] Separately, the FT-IR spectra of the surface modified nanodiamond obtained in Example 1 are shown in Figure 2 The FT-IR spectrum of the surface modified nanodiamond obtained in Example 2 is shown in Figure 3 The FT-IR spectrum of the surface modified nanodiamond obtained in Example 3 is shown in Figure 4 The FT-IR spectrum of the surface modified nanodiamond obtained in Example 4 is shown in Figure 5 The FT-IR spectrum of the surface modified nanodiamond obtained in Example 5 is shown in Figure 6 The FT-IR spectrum of the surface modified nanodiamond obtained in Comparative Example 1 is shown in Figure 7 In Examples 1 to 3, at 1705 to 1717 cm -1 The C=O peak derived from the carbamate bond was observed at 1521 cm -1NH peaks derived from carbamate bonds were observed near 1736 cm-1. It can be inferred that in Examples 1 to 3, nanodiamonds with carbamoyl bonds derived from isocyanate and hydroxyl groups on the polyglycerol chain were obtained. The characteristic peaks observed in the surface-modified nanodiamonds obtained in Examples 1 to 3 are peaks not observed in the nanodiamonds obtained in Comparative Example 1. In addition, in Example 4, the peak at 1736 cm-1 was observed at 1736 cm-1. -1 A strong C=O peak derived from the ester bond was observed near 1734 cm -1 A strong C=O peak derived from an ester bond was observed nearby. The strong and sharp C=O peak observed in Examples 4 and 5 is a peak not observed in the nanodiamond obtained in Comparative Example 1.

[0178] < 13 C-NMR analysis>

[0179] The surface modified nanodiamond obtained in Example 2 was subjected to 13 C-NMR analysis. Specifically, the dry powder of the surface-modified nanodiamond obtained in Example 2 and the hydrophilic ND particles modified with polyglycerol (PG-ND) were dispersed in deuterated DMSO (0.3% tetramethylsilane) using an ultrasonic cleaner and then subjected to C-NMR analysis using a Brucker AVANCE (600 MHz). 13 C-NMR spectrum measurement: The measurement was performed at 25°C and with a cumulative frequency of 200,000.

[0180] The surface modified nanodiamond obtained in Example 2 13 C-NMR spectrum Figure 8 As shown. In Example 2, peak a near 13-14 ppm and peak b near 19-20 ppm and 31-32 ppm were observed. These peaks come from the hydroxyl groups on the polyglycerol chain being blocked by alkyl chains. In addition, peak d derived from the C=O group was observed near 155-157 ppm, which comes from the hydroxyl groups on the polyglycerol chain being blocked by alkyl isocyanate. On the other hand, the hydrophilic ND particles (PG-ND particles) modified with polyglycerol 13 In the C-NMR spectrum, only peaks at around 58 to 82 ppm derived from the polyglycerol chain and peaks at around 24 to 38 ppm derived from the nanodiamond were observed.

[0181] Modifications of the present invention will be described below.

[0182] [Supplementary Note 1] A surface-modified nanodiamond comprising a nanodiamond particle and a surface-modifying group for surface-modifying the nanodiamond particle, wherein the surface-modifying group has a polyglycerol chain, and hydrogen atoms of at least a portion of hydroxyl groups in the polyglycerol chain are substituted with a monovalent organic group.

[0183] [Supplement 2] The surface-modified nanodiamond according to Supplement 1, wherein

[0184] The polyglycerol chain is bonded to the nano-diamond particle via a single bond or a divalent group.

[0185] [Supplement 3] The surface-modified nanodiamond according to Supplement 2, wherein:

[0186] The above-mentioned divalent group is an amino group (-NH-), an ether bond (-O-), an ester bond (-C(=O)O-), a phosphinate group (-PH(=O)O-), a thioether bond (-S-), a carbonyl group (-C(=O)-), an amide group (-C(=O)-NH-), a carbamate bond (-NH-C(=O)-O-), an imide bond (-C(=O)-NH-C(=O)-), a thiocarbonyl group (-C(=S)-), a siloxane bond (-Si-O-), a divalent hydrocarbon group, or a group in which two or more thereof are bonded (preferably a single bond, -NH-, -O-, -C(=O)O-, -PH(=O)O-, -S-, and more preferably a single bond).

[0187] [Supplement 4] The surface-modified nanodiamond according to any one of Supplements 1 to 3, wherein

[0188] The monovalent organic group is a group represented by the following formula (1).

[0189] -XR (1)

[0190] [In formula (1), X represents a single bond, -C(=O)-, or -C(=O)-NH-. R represents a monovalent organic group, and the atom bonded to X is a carbon atom.]

[0191] [Supplement 5] The surface-modified nanodiamond according to Supplement 4, wherein

[0192] The above R is a substituted or unsubstituted hydrocarbon group (preferably an alkyl group, more preferably an alkyl group having 1 to 18 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, particularly preferably an ethyl group, a butyl group, or a hexyl group).

[0193] [Supplement 6] The surface-modified nanodiamond according to any one of Supplements 1 to 5, wherein

[0194] The surface modifying group is a polyglycerol chain-containing surface modifying group represented by the following formula (2).

[0195] -Y-(C3H6O2)p-(C3H5O2R 1 )q-OR 2 (2)

[0196] [In formula (2), p and q each represent the average degree of polymerization of the repeating units in parentheses, p is a value greater than or equal to 0, q is a value greater than or equal to 0, and p+q is a value greater than or equal to 1 (preferably 1 to 100, more preferably 2 to 40, and even more preferably 3 to 30). 1 Represents a monovalent organic group. [-OR 2 ] indicates the end of the polyglycerol chain, R 2 represents a hydrogen atom or a monovalent organic group. 2 When Y is a hydrogen atom, q represents a value greater than 0. Y represents a single bond or a divalent group (preferably a single bond, -NH-, -O-, -C(=O)O-, -PH(=O)O-, -S-, and more preferably a single bond), and the bond arm extending to the left from Y is bonded to the nanodiamond particle. The oxygen atom bonded to Y in formula (2) may be an oxygen atom in a structural unit marked with p or an oxygen atom in a structural unit marked with q. 2 The carbon atom in formula (2) to be bonded may be a carbon atom in a structural unit marked with p or a carbon atom in a structural unit marked with q.]

[0197] [Supplement 7] The surface-modified nanodiamond according to Supplement 6, wherein

[0198] [q / (p+q)] in the above formula (2) is 0.6 or more (preferably 0.8 to 1.0).

[0199] [Supplement 8] The surface-modified nanodiamond according to Supplement 4 or 5, wherein

[0200] In the above formula (1), R represents an alkyl group.

[0201] [Supplement 9] The surface-modified nanodiamond according to Supplement 4 or 5, wherein

[0202] In the above formula (1), R represents an alkyl group having 1 to 18 carbon atoms.

[0203] [Supplement 10] The surface-modified nanodiamond according to Supplement 4 or 5, wherein

[0204] In the above formula (1), R represents an ethyl group, a butyl group, or a hexyl group.

[0205] [Supplement 11] The surface-modified nanodiamond according to any one of Supplements 1 to 10, wherein

[0206] The mass ratio of the nanodiamond particles in the surface-modified nanodiamond to the surface-modifying groups [nanodiamond particles / surface-modifying groups] is 0.5 to 1.0 (preferably 0.6 to 0.8).

[0207] [Supplement 12] The surface-modified nanodiamond according to any one of Supplements 1 to 11, wherein

[0208] In the FT-IR spectrum of the surface-modified nanodiamond, the -1 Nearby and 1700~1730cm -1 There are absorption peaks near them.

[0209] [Supplement 13] The surface-modified nanodiamond according to any one of Supplements 1 to 11, wherein

[0210] In the FT-IR spectrum of the surface-modified nanodiamond, the -1 There is an absorption peak near

[0211] [Supplement 14] The surface-modified nanodiamond according to any one of Supplements 1 to 13, wherein

[0212] In the above surface modified nanodiamond 13 In the C-NMR spectrum, there is a peak near 60 to 85 ppm.

[0213] [Supplement 15] The surface-modified nanodiamond according to any one of Supplements 1 to 14, wherein

[0214] In the above surface modified nanodiamond 13 In the C-NMR spectrum, there is a peak near 140 to 200 ppm.

[0215] [Supplement 16] The surface-modified nanodiamond according to any one of Supplements 1 to 15, wherein

[0216] In the above surface modified nanodiamond 13 In the C-NMR spectrum, there is a peak near 5 to 45 ppm.

[0217] [Supplement 17] The surface-modified nanodiamond according to any one of Supplements 1 to 16, wherein

[0218] The surface-modified nanodiamond was dispersed in a Hildebrand solubility parameter (δ) of 10 (cal / cm 3 ) 1 / 2The median particle size in the case of at least one organic dispersion medium is 5 to 100 nm (preferably 5 to 80 nm, more preferably 5 to 50 nm).

[0219] [Supplement 18] The surface-modified nanodiamond according to any one of Supplements 1 to 17, wherein

[0220] The particle size (D50) of the surface-modified nanodiamond is 400 nm or less (preferably 300 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less).

[0221] [Supplement 19] The surface-modified nanodiamond according to any one of Supplements 1 to 18, wherein

[0222] The particle size (D90) of the surface-modified nanodiamond is 500 nm or less (preferably 180 nm or less, more preferably 170 nm or less).

[0223] [Supplement 20] The surface-modified nanodiamond according to any one of Supplements 1 to 19, wherein

[0224] The nano-diamond particles include detonation-processed nano-diamonds (preferably air-cooled detonation-processed nano-diamonds).

[0225] [Supplement 21] A nano-diamond dispersion composition comprising: a dispersion medium, and the surface-modified nano-diamond according to any one of Supplements 1 to 20 dispersed in the dispersion medium.

[0226] [Supplementary Note 22] The nano-diamond dispersion composition according to Supplementary Note 21, wherein

[0227] The above-mentioned dispersion medium contains a cyclic ether or a chain ketone (preferably a chain ketone).

[0228] [Supplement 23] The nano-diamond dispersion composition according to Supplement 21 or 22, wherein

[0229] The content ratio of the nano-diamond particles in the nano-diamond dispersion composition is 0.1 mass ppm to 10 mass %.

[0230] [Supplement 24] The nano-diamond dispersion composition according to any one of Supplements 21 to 23, wherein

[0231] The content ratio of the dispersion medium in the nano-diamond dispersion composition is 90 to 99.9999 mass %.

[0232] [Supplement 25] The nano-diamond dispersion composition according to any one of Supplements 21 to 24, wherein

[0233] The total content of the surface-modified nanodiamond and the dispersion medium is 70% by mass or more (preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 99% by mass or more) relative to the total amount of the nanodiamond dispersion composition.

[0234] [Supplement 26] The nano-diamond dispersion composition according to any one of Supplements 21 to 25, wherein

[0235] The average dispersed particle size (D50) of the nano-diamond particles in the nano-diamond dispersion composition is 100 nm or less (preferably 60 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less).

[0236] [Supplement 27] The nano-diamond dispersion composition according to any one of Supplements 21 to 26, wherein

[0237] The nano-diamond dispersion composition has a haze value of 5 or less (preferably 3 or less, more preferably 1 or less).

[0238] [Supplementary Note 28] A method for producing surface-modified nanodiamonds, the method comprising:

[0239] A surface-modified nanodiamond (A) is reacted with one or more compounds selected from alcohol (B1), isocyanate (B2), and carboxylic acid chloride (B3) to obtain the surface-modified nanodiamond described in any one of Supplements 1 to 20, wherein the surface-modified nanodiamond (A) has nanodiamond particles and a surface-modifying group for surface-modifying the nanodiamond particles, wherein the surface-modifying group includes a polyglycerol chain having a hydroxyl group.

[0240] [Supplement 29] The method for producing surface-modified nanodiamond according to Supplement 28, wherein:

[0241] The alcohol (B1) contains C 1-18 Alcohol (preferably ethanol, n-butanol, n-hexanol).

[0242] [Supplement 30] The method for producing surface-modified nanodiamond according to Supplement 28, wherein:

[0243] The above isocyanate (B2) contains alkyl isocyanate (preferably C 1-18 isocyanate, more preferably ethyl isocyanate, n-butyl isocyanate, n-hexyl isocyanate).

[0244] [Supplement 31] The method for producing surface-modified nanodiamond according to Supplement 28, wherein:

[0245] The carboxylic acid chloride (B3) comprises an acyl chloride (preferably an acyl group having a carbon number of C 1-19 alkyl acyl chloride, more preferably valeryl chloride).

[0246] [Supplement 32] The method for producing a surface-modified nanodiamond according to any one of Supplements 28 to 31, wherein

[0247] The ratio (former:latter, mass ratio) of the surface-modified nanodiamond (A) to the alcohol (B1), isocyanate (B2), and / or carboxylic acid chloride (B3) provided for the reaction is 2:1 to 1:80.

[0248] [Supplement 33] The method for producing a surface-modified nanodiamond according to any one of Supplements 28 to 32, wherein

[0249] The nanodiamond in the surface-modified nanodiamond (A) comprises a detonation-processed nanodiamond (preferably a gas-cooled detonation-processed nanodiamond).

Claims

1. A surface-modified nanodiamond, comprising a nanodiamond particle and a surface-modifying group for surface-modifying the nanodiamond particle, The surface modification group has a polyglycerol chain, and at least a portion of hydrogen atoms of hydroxyl groups in the polyglycerol chain are substituted by a monovalent organic group having a linking group. The monovalent organic group having a linking group is a group represented by the following formula (1): -XR(1) In formula (1), X represents -C(=O)- or -C(=O)-NH-, R represents a monovalent organic group, and the atom bonded to X is a carbon atom. The surface modification group is a polyglycerol chain-containing surface modification group represented by the following formula (2): -Y-(C3H6O2)p-(C3H5O2R 1 )q-OR 2 (2) In formula (2), p and q represent the average polymerization degree of the repeating units in the parentheses, respectively, p is a value greater than 0, q is a value greater than 0, and p+q is a value greater than 1. R 1 represents the monovalent organic group having a connecting group, -OR 2 Indicates the end of the polyglycerol chain, R 2 represents a hydrogen atom or the monovalent organic group having a connecting group, wherein In R 2 In the case of a hydrogen atom, q represents a value greater than 0, Y represents a single bond or a divalent group, The bond arm extending to the left from the Y is bonded to the nanodiamond particle.

2. The surface-modified nanodiamond according to claim 1, wherein The divalent group is one of an amino group, an ether bond, an ester bond, a phosphinate group, a thioether bond, a carbonyl group, an amide group, a carbamate bond, an imide bond, a thiocarbonyl group, a siloxane bond and a divalent hydrocarbon group, or a group formed by bonding two or more of them.

3. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the above formula (1), R represents an alkyl group.

4. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the above formula (1), R represents an alkyl group having 1 to 18 carbon atoms.

5. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the above formula (1), R represents an ethyl group, a butyl group, or a hexyl group.

6. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the formula (2), p, q, and p+q are all 1 to 100.

7. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the formula (2), p, q, and p+q are all 3 to 30.

8. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the above formula (2), p and q satisfy: [q / (p+q)] is greater than or equal to 0.

6.

9. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the formula (2), p and q satisfy: [q / (p+q)] is 0.8 to 1.

0.

10. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the formula (2), p, q, and p+q are all 1 to 100, and R in the formula (1) represents an alkyl group.

11. The surface-modified nanodiamond according to claim 1 or 2, wherein: The mass ratio of the nano-diamond particles in the surface-modified nano-diamond to the surface-modified groups is 0.5 to 1.

0.

12. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the FT-IR spectrum of the surface-modified nanodiamond, the -1 Nearby and 1700~1730cm -1 There are absorption peaks near them.

13. The surface-modified nanodiamond according to claim 1 or 2, wherein: In the FT-IR spectrum of the surface-modified nanodiamond, at 1730-1750cm -1 There is an absorption peak near 14. The surface-modified nanodiamond according to claim 1 or 2, wherein: On the surface modified with nanodiamond 13 In the C-NMR spectrum, there is a peak near 60 to 85 ppm.

15. The surface-modified nanodiamond according to claim 1 or 2, wherein: On the surface modified with nanodiamond 13 In the C-NMR spectrum, there is a peak near 140 to 200 ppm.

16. The surface-modified nanodiamond according to claim 1 or 2, wherein: On the surface modified with nanodiamond 13 In the C-NMR spectrum, there is a peak near 5 to 45 ppm.

17. The surface-modified nanodiamond according to claim 1 or 2, wherein: The surface-modified nanodiamond was dispersed in a Hildebrand solubility parameter δ of 10 (cal / cm 3 ) 1 / 2 The median particle size of at least one organic dispersion medium is 5 to 100 nm.

18. The surface-modified nanodiamond according to claim 17, wherein: The median particle size is 5 to 50 nm.

19. The surface-modified nanodiamond according to claim 1 or 2, wherein: The particle size D50 of the surface-modified nanodiamond is less than 400 nm.

20. The surface-modified nanodiamond according to claim 1 or 2, wherein: The particle size D90 of the surface modified nanodiamond is less than 500 nm.

21. A nano-diamond dispersion composition comprising: Dispersion medium, and The surface-modified nanodiamond according to claim 1 or 2 is dispersed in the dispersion medium.

22. The nano-diamond dispersion composition according to claim 21, wherein: The dispersion medium contains a cyclic ether or a chain ketone.

23. The nano-diamond dispersion composition according to claim 21, wherein: The content ratio of the surface-modified nano-diamond in the nano-diamond dispersion composition is 0.1 ppm by mass to 10% by mass.

24. The nano-diamond dispersion composition according to claim 21, wherein: The content ratio of the dispersion medium in the nano-diamond dispersion composition is 90 to 99.9999 mass %.

25. The nano-diamond dispersion composition according to claim 21, wherein The total content of the surface-modified nanodiamond and the dispersion medium is 70% by mass or more relative to the total amount of the nanodiamond dispersion composition.

26. The nano-diamond dispersion composition according to claim 21, wherein: The total content of the surface-modified nanodiamond and the dispersion medium is 90% by mass or more relative to the total amount of the nanodiamond dispersion composition.

27. The nano-diamond dispersion composition according to claim 21, wherein: The total content of the surface-modified nanodiamond and the dispersion medium is 99% by mass or more relative to the total amount of the nanodiamond dispersion composition.

28. The nano-diamond dispersion composition according to claim 21, wherein The average dispersed particle size D50 of the surface-modified nano-diamonds in the nano-diamond dispersion composition is less than 100 nm.

29. The nano-diamond dispersion composition according to claim 21, wherein: The nano-diamond dispersion composition has a haze value of 5 or less.

30. The nano-diamond dispersion composition according to claim 21, wherein: The nano-diamond dispersion composition has a haze value of 1 or less.

31. A method for producing surface-modified nanodiamond, the method comprising: The surface-modified nanodiamond according to claim 1 or 2 is obtained by reacting a surface-modified nanodiamond having a nanodiamond particle and a surface-modifying group for surface-modifying the nanodiamond particle with one or more compounds selected from alcohol, isocyanate and carboxylic acid chloride, wherein the surface-modified group comprises a polyglycerol chain having a hydroxyl group.

32. The method for producing surface-modified nanodiamond according to claim 31, in, The alcohol comprises C 1-18 alcohol.

33. The method for producing surface-modified nanodiamond according to claim 31, in, The isocyanate comprises an alkyl isocyanate.

34. The method for producing surface-modified nanodiamond according to claim 31, in, The carboxylic acid chloride comprises an acid chloride.

35. The method for producing surface-modified nanodiamond according to claim 31, in, The ratio of the surface-modified nanodiamond to be subjected to the reaction to one or more compounds selected from alcohol, isocyanate and carboxylic acid chloride is 2:1 to 1:80 in terms of mass ratio.

36. The method for producing surface-modified nanodiamond according to claim 31, in, The nanodiamonds in the surface-modified nanodiamonds provided for the reaction include detonation-processed nanodiamonds.

Citation Information

Patent Citations

  • Surface-modified nanodiamond and producing method thereof

    JP2010248023A

  • Surface-modified nanodiamond with controlled size

    JP2012082103A

  • Rainwater infiltration prevention cover

    JP2019105065A

  • Surface-modified nanodiamond and its producing method

    US20100261926A1